A Primary Pulmonary Glomus Tumor: A Case Report and Review of the Literature - Yasushi Ariizumi; Hirotaka Koizumi; Masahiro Hoshikawa; Takuo Shinmyo; Kouji Ando; Atsushi Mochizuki; Ayako Tateishi; Masatomo Doi; Mieko Funatsu; Ichirou Maeda; Masayuki Takagi (Case Reports in Pathology)
A case of a glomus tumor originating from the lung is reported. A 43-year-old female had undergone resection of a right lung tumor following a clinical diagnosis of carcinoid, sclerosing hemangioma, or other sarcoma. Histologically, the tumor comprised uniform small round to oval cells with centrally located nucleus, a clear cytoplasm, and apparent cell borders. The tumor also showed a focally hemangiopericytomatous pattern with irregularly branching or dilated vessels. Electron microscopy revealed smooth muscle differentiation of the tumor cells. Immunostaining further revealed that the tumor cells expressed smooth muscle actin, h-caldesmon, muscle specific actin (HHF-35), but not cytokeratin, epithelial membrane antigen, synaptophysin, or chromogranin A. Based on these findings, a diagnosis of primary pulmonary glomus tumor was established. Glomus tumors of the lung are very rare and only 21 cases have been reported to date. The histological features of the present tumor and the relevant literature are discussed.